Geology of the Parliament Buildings 5: Geology of the Manitoba Legislative Building - Brisbin, W.; Young, Graham; Young, Jeff (Geoscience Canada, 2005)
SUMMARY The Manitoba Legislative Building was designed by Frank Worthington Simon, assisted by Henry Boddington III, architects from Liverpool, England. The building style is neoclassical, incorporating Greek, Roman and Egyptian motifs and elements. Construction was completed early in 1920 and the building was dedicated July 15, 1920, on the fiftieth anniversary of the Province. The building is located in central Winnipeg, close to the north bank of the Assiniboine River and rests on 14 m of glacial Lake Agassiz clays over till and limestone bedrock. The mass of the building is supported by 421 concrete caissons that extend through the clays to indurated till or bedrock. Steel frames rest on the caissons and support bearing walls constructed of bricks manufactured from Manitoba shale and clay. Dimension stones decorate the bearing walls inside and outside, and the floors and stairways within. Each type of stone has its own decorative characteristics and each records geologic processes at different times in Earth history. The predominant dimension stone both outside and inside the building is Manitoba Tyndall Stone. Grey, pink and red Tennessee marbles are from the southern Appalachians. Botticino marble was quarried in the foothills of the Alps in northern Italy. Ordovician black marble and Verde Antique are from the Vermont-New York region in the northern Appalachians. Missisquoi marble is from quarries in southern Québec near Philipsburg, and also represents a northern Appalachian source. Bedford limestone, used for most of the statuary, is from south-central Indiana. Butler granite from Ignace, Ontario, was used for steps and floor surfaces of all four porticos. Red marble breccia, used to decorate most fireplaces, may have come from northern France.